Investigation of the Relationship between 4-Step Walking Distance, 6-m Walking Speed, and 5-Times Sit-To-Stand Test in Patients Undergoing Gastrointestinal Surgery - Kimura, Sae; Mikami, Shinya; Kobayashi, Shinjiro; Otsubo, Takehito (Journal of St. Marianna University, 2024)
[Abstract] Objective: We investigated the correlation between the distance walked in the first 4 steps, 6-m walking speed test and 6-m walking speed, and 5-times sit-to-stand test to establish an alternative method for evaluating walking speed, a criterion for diagnosing sarcopenia. Methods: We included in this study 50 patients who underwent elective abdominal surgery between October 2023 and May 2024 at our department. The main analyses were measurements of distance traveled over the first 4 steps taken at the start of the test, 6-m walking speed, 5-times sit-to-stand test, and correlations of 4-step walking distance with 6-m walking speed and with 5-times sit-to-stand test. Results: The mean (range) 6-m walking speed was 1.224 (0.636-2.073) m/sec, and the mean 4-step walking distance was 2.485 (1.88-3.68) m, which showed a significant positive correlation with a correlation coefficient of 0.72 (95% confidence interval [CI]: 0.5559-0.8332, p<0.0001). Based on the receiver operating characteristic curve derived from logistic regression analysis, the cut-off value for the 4-step walking distance was 2.24 m when the 6-m walking speed was<1.0 m/sec. The mean value of the 5-times sit-to-stand test was 9.55 s. The 4-step walking distance and the 5-times sit-to-stand test time were significantly correlated (correlation coefficient: -0.32, 95% CI: -0.5484 - -0.0442, p=0.0241). Conclusion: There was a correlation between the 6-m walking speed and the distance walked over the first 4 steps, suggesting that a 4-step walking distance of less than 2.24 m may indicate a decline in physical function.